Peranan amitriptilin pada pengobatan dispepsia fungsional - Indra Mustawa; Supriatmo dr; Atan Baas Sinuhaji (Majalah Kedokteran Nusantara The Journal Of Medical School, 2012)
Functional dyspepsia is common in adolescents. School absenteeism and poor quality of life are associated with the severity of the symptoms. Pathophysiology of functional dyspepsia is very heterogeneous. Currently there is no satisfactory therapy in the treatment of functional dyspepsia. Biopsychosocial factor is one of the contributing factor causing the symptoms of functional dyspepsia. One of the alternative therapy is Tricyclic antidepressant (TCA) such as amitriptyline. Amitriptyline is theoretically advantageous because their overall effect on the brain-gut axis, both at the center and in the intestine.Keywords: amitriptyline; functional dyspepsia; adolescent